2001
DOI: 10.1016/s0893-133x(00)00189-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Kainate Receptor Expression in Prefrontal Cortex in Schizophrenia

Abstract: A growing literature suggests glutamatergic dysfunction in schizophrenia. Perhaps the strongest evidence for glutamatergic involvement in this illness is that dissociative anesthetics, especially phencyclidine and ketamine, can cause a schizophreniform psychosis in normal humans, and worsen psychotic symptoms in persons with schizophrenia (Itil et al. 1967;Javitt and Zukin 1991;Krystal et al. 1994;Lahti et al. 1995;Luby et al. 1962). These drugs are uncompetitive inhibitors of the NMDA subtype of glutamate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 34 publications
4
39
1
Order By: Relevance
“…Our finding of decreased cortical kainate receptors in BA 9 partially replicates another study, which showed a decrease in kainate binding in the prefrontal cortex (BA 9,11,32,and 46) in schizophrenia (Meador-Woodruff et al, 2001a). However, this earlier study found decreases in KA2 mRNA and increased GluR7 mRNA in tissue from the same subjects, which contrasts with our finding of decreased GluR5 mRNA.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our finding of decreased cortical kainate receptors in BA 9 partially replicates another study, which showed a decrease in kainate binding in the prefrontal cortex (BA 9,11,32,and 46) in schizophrenia (Meador-Woodruff et al, 2001a). However, this earlier study found decreases in KA2 mRNA and increased GluR7 mRNA in tissue from the same subjects, which contrasts with our finding of decreased GluR5 mRNA.…”
Section: Discussionsupporting
confidence: 68%
“…This is demonstrated by studies that have investigated multiple cortical regions and shown an increase in the NMDA receptor in BA 22 but not BA 10 (Nudmamud and Reynolds, 2001) from subjects with the disorder. Similarly, decreases in kainate receptors in the prefrontal but not the occipital cortex (Meador-Woodruff et al, 2001a) have been reported. Thus, to avoid introducing cortical regional variation in changes in glutamate receptors as a confounding variable in discussion of our study in BA 9, our findings will be compared to other studies in either this CNS region or in the dorsolateral prefrontal cortex (DLPFC; BA 9 and 46) from subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present study no changes in [ 3 H]kainate binding were observed in the ACC between the schizophrenia and control groups. Interestingly, kainate receptor binding has been reported to be elevated in multiple cortical areas in schizophrenia (Deakin et al 1989;Nishikawa et al 1983) and decreased in prefrontal cortex (Meador-Woodruff et al 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Recently it has been demonstrated that the GRIK3 gene encoding for the ionotropic glutamate receptor kainate 3 contains a functional polymorphism (T928G) leading to the substitution of a serine with an alanine in position 310 of the protein sequence. [8][9][10][11] We performed an association study between the ser310ala GRIK3 polymorphism and schizophrenia in a sample of 99 schizophrenic patients and 116 controls. We found a significant difference in the genotype distribution and in particular considering the ala allele as dominant (P = 0.0105, odds ratio (OR) 2.031, 95% confidence interval (CI) 1.177-3.504).…”
mentioning
confidence: 99%